(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The importance of the research stems from the fact that early warning indicators provide a permanent and continuous tool for guidance and warning to decision-makers and policy-makers about the possibility of the banking system being affected by the financial crisis before it occurs, in order to take the necessary preventive policies and measures to protect banks from the impact of these crises, as the banking sector is the sector most affected by these crises and has an effective influence on economic activities. Therefore, we chose the research topic, as we will try to apply early warning indicators and macroeconomic variables indicators to two important banks, namely Rafidain Bank and the Iraqi Islamic Bank for Investment and Development, to determine the extent of their impact on financial crises in light of the economic transformation to a market economy according to the new economic policy in Iraq, noting that there is an early warning report for the banking sector issued by the Statistics and Research Department of the Central Bank of Iraq regarding the banking sector, and an early warning report regarding various economic sectors issued by the National Accounts Directorate of the Statistics and Geographic Information Systems Authority in the Ministry of Planning, which are quarterly reports . The above two banks were chosen because Rafidain Bank, which is owned by the public sector, is the main bank that has had an effective presence in the Iraqi economy for a long period of time, while the Iraqi Islamic Bank for Investment and Development is one of the most important and largest Islamic banks in Iraq and has effective contributions to financing investment projects in Iraq according to the provisions of Islamic Sharia . The study reached a set of recommendations, the most important of which are: Every bank must establish a forecasting department. Early With banking crises and its purpose more capacity Banks on Usage The competent For its resources And confront Risks that may You face it when Doing In its work and ensuring the ability of banks to continue, we propose to adhere to the decisions of the Basel Committee regarding reliance on supporting capital consisting of reserves, long-term loans received and long-term allocations in order to provide the necessary cash liquidity. We also propose to shift the activity of banks to Islamic banks because Islamic banks are not affected by financial crises because they do not trade in debt, but rather practice their activity through participation in capital and thus achieve profitability.